Cyber Security Analysis on Small Medium Enterprise's Online Shop - Ahnes Montoh, I Gusti Ayu Mirahyanti, Tessa Rantung (International Journal of Information Technology and Education, 2021)
Competition in the increasingly competitive business world has resulted in people using technology or companies carrying out business strategies in order to win or survive in the world of e-commerce. This study aims to analyze matters related to cybercrime, especially regarding the threat from cybercrime itself to Yhummy online shop. This study specifically discusses how cybercrime occurs in the world of e-commerce, especially in the Yhummy online shop. This puts the attitude factor in each user's behavior or brainware that deviates from the rules of the technology world. The method used in this study is a survey method conducted on an online shop. The type of data used is primary data which is obtained directly from the answers of the Yhummy olshop owner and the respondent's questionnaire. Direct interviews to the owner of the Yhummy olshop and to respondents whose areas are still within reach. The sampling technique used was non-probability sampling using purposive sampling method. The results showed that the characteristics of online shopping respondents were dominated by women and had an age range of 16 to 25 years. Most of them are students or college students. The results of this study also show that the quality of trust from Yhummy olshop customers is very high. It can be seen that male consumers have a slightly lower percentage than women, this shows that male interest in online shops is not as great as female interest. However, it is possible that cybercrime cases can also be caused by men.